Agreement between Subjective and Objective Parameters Using Meibography for Assessment of Dry Eye Syndrome - Taimoor, Ijlal; Naqvi, Syed Abid Hassan; Khan, Taimoor Ashraf; Naeem, Saquib; Yousaf, Waseem; Ghani, Muhammad Usman (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the agreement between subjective and objective parameters using meibography. Study Design: Cross-sectional observational study. Place and Duration of Study: Armed Forces Institute of Ophthalmology (AFIO), Rawalpindi Pakistan from August 2021 till February 2022. Methodology: 100 patients were included in the study. Non-contact infra-red meibography was performed on each patient. Subjective assessment was done using the four-grade and five-grade scales while objective assessment was done by applying computerized grading. Results: A total of one hundred (n=100) patients participated in the study. Out of total, 60% patients were male and 40% were females, with a mean age 42.25±14.9 years. There was statistically significant difference was seen Session I OII vs Session II OII as p-value <0.001 in Grade-4, Session-I OIII vs Session-II OIII as p-value <0.001 in Grade-5. There was not statistically significant difference seen in Computerized Grading (100-grade scale) as p-value >0.05. Correlations between observers was best with the 5-grade scale followed by the computerized 100-grade scale and 4-grade scale. Conclusions: We found that the reliability of the 5-grade scale was poorer to that of the 4-grade scales. We also concluded that computerized grading offers a better intra and inter-observer assessment.